Monoclonal Gammopathy of Undetermined Significance (MGUS) in a Man with Fragile X-associated Tremor/Ataxia Syndrome - Tanjung A. Sumekar; Aneel A. Ashrani; Tri I. Winarni; Randi J. Hagerman (Case Reports in Genetics)
We report the clinical presentation and laboratory findings of a 69-year-old man with fragile X-associated tremor ataxia syndrome (FXTAS), a progressive neurodegenerative disorder, who was noted to have monoclonal gammopathy of undetermined significance (MGUS), a plasma cell proliferative disorder and a precursor disease of multiple myeloma. Both MGUS and FXTAS are associated with microRNA (miRNA) dysregulation. We speculate that individuals with FXTAS may be predisposed to MGUS and further studies are warranted regarding this association.